Identifying and Supporting Children with Special Needs in Inclusive Elementary Schools: Challenges and Strategies - Hermita, Neni; Barokah, Rifqa Gusmida Syahrun; Putri, Ayu Manca; Dita, Rokiya; Nurbaiti, Siti; Ardiaulya, Vidola (Institut of Shanti Bhuana, 2025)
This study examines the identification process and challenges in supporting students with special needs at SDN 31 Pekanbaru, an inclusive elementary school. Using a qualitative case study approach, data were collected through classroom observations, interviews, document analysis, and standardized screening tools. Teachers and researchers assessed students from Grades 1 to 6 and identified five students with special needs: three slow learners and two with ADHD. Findings indicate that the school lacks a formal identification procedure, relying instead on parental reports and personal observations. The absence of specialized training also poses challenges in providing effective interventions. Key challenges include inadequate teacher preparedness, limited resources, and low parental involvement due to social stigma and financial constraints. Although inclusive education policies exist, the current curriculum does not fully accommodate students with diverse learning needs. This study recommends structured teacher training, increased resource allocation, and educational programs for parents. Further research should explore the long-term impact of inclusive education, the effectiveness of teacher training, and strategies to enhance parental involvement in fostering a more inclusive learning environment